2010
DOI: 10.1038/modpathol.2009.170
|View full text |Cite
|
Sign up to set email alerts
|

HDM4 is overexpressed in mantle cell lymphoma and its inhibition induces p21 expression and apoptosis

Abstract: In mouse models and cell lines, murine double minute 2 (MDM2) and MDM4 have been shown to synergistically promote proteasome-mediated degradation of p21 and p53. MDM4 also inhibits p53-mediated transcriptional activation of p21. p53 expression results in increased p21 expression, a negative cell-cycle regulatory protein and an inhibitor of cyclin D1. As mantle cell lymphoma is characterized by cyclin D1 overexpression, we assessed for human homolog of MDM4 (HDM4) expression and its effect on p21 in mantle cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 35 publications
1
15
1
Order By: Relevance
“…This result positions Mdmx protein as an important inhibitor of the p53 pathway especially in APL as well as in CN-AML. Our findings are in line with reports that revealed upregulated Mdmx protein in various human malignancies [3235, 37, 38, 40] including AML with complex karyotype [41] and showed the ability of Mdmx to inhibit p53 activity in AML cell lines [135]. Here we present evidence for the link between Mdmx levels and functional inhibition of p53 in CN-AML and APL patients.…”
Section: Discussionsupporting
confidence: 93%
“…This result positions Mdmx protein as an important inhibitor of the p53 pathway especially in APL as well as in CN-AML. Our findings are in line with reports that revealed upregulated Mdmx protein in various human malignancies [3235, 37, 38, 40] including AML with complex karyotype [41] and showed the ability of Mdmx to inhibit p53 activity in AML cell lines [135]. Here we present evidence for the link between Mdmx levels and functional inhibition of p53 in CN-AML and APL patients.…”
Section: Discussionsupporting
confidence: 93%
“…Murine double minute 4 (MDM4), also known as MDMx, is amplified or overexpressed in various human cancers (Danovi et al ., ; Han et al ., ; Li et al ., ; Liang et al ., ; Riemenschneider et al ., ; Wade et al ., ). Thus, overexpression of MDM4 appears to favor cancer cell survival.…”
Section: Introductionmentioning
confidence: 99%
“…MDMX-S is overexpressed in some carcinomas and sarcomas (99, 122, 123). The overexpression of MDMX and MDMX-S has also been demonstrated in mantle cell lymphoma, in which it has been suggested that it suppresses p21 and therefore promotes cell-cycle progression (124). …”
Section: Mdm2 and Mdmx In Human Cancermentioning
confidence: 99%